1996
DOI: 10.1002/j.1460-2075.1996.tb00531.x
|View full text |Cite
|
Sign up to set email alerts
|

The conserved amino-terminal domain of hSRP1 alpha is essential for nuclear protein import.

Abstract: Nuclear proteins are targeted through the nuclear pore complex (NPC) in an energy‐dependent reaction. The import reaction is mediated by nuclear localization sequences (NLS) in the substrate which are recognized by heterodimeric cytoplasmic receptors. hSRP1 alpha is an NLS‐binding subunit of the human NLS receptor complex and is complexed in vivo with a second subunit of 97 kDa (p97). We show here that a short amino‐terminal domain in hSRP1 alpha is necessary and sufficient for its interaction with p97. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
268
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(278 citation statements)
references
References 34 publications
9
268
1
Order By: Relevance
“…PHAX has to recycle to the nucleus to mediate multiple rounds of U snRNA export+ We have previously shown that PHAX moves into the nucleus upon injection into the cytoplasm of Xenopus oocytes, whereas it is not apparently exported upon injection into the nucleus in the absence of U snRNAs (Ohno et al+, 2000; see also below)+ This means that although PHAX can shuttle between the nucleus and the cytoplasm, its steadystate localization in Xenopus oocytes is nuclear+ To investigate if this is also the case in mammalian cells, we performed indirect immunofluorescence staining of HeLa cells with affinity purified anti-PHAX antibody+ As shown in Figure 1A, strong PHAX signal was detected in the nucleoplasm (excluding nucleoli) with little if any cytoplasmic signal, indicating that nuclear localization of PHAX at steady state is not a Xenopus oocytespecific phenomenon+ Although the nucleoplasmic staining was not entirely uniform, and several brighter spots were often seen, further analysis of PHAX distribution has not been performed+ Next, attempts were made to characterize the nuclear localization signal (NLS) of PHAX in Xenopus oocyte injection experiments+ When 35 S-methionine labeled PHAX was injected into the cytoplasm together with two control proteins, PHAX, as well as the positive control CBP80, moved to the nucleus, whereas the negative control (GSTM10) stayed in the cytoplasm (Fig+ 1B, lanes 1-4)+ Nuclear migration of PHAX was severely inhibited by coinjection of either the importin b binding domain of importin a (IBB; Görlich et al+, 1996a;Weis et al+, 1996) or BSA-conjugated with NLS peptides derived from SV40 T antigen (BSA-NLS; Goldfarb et al+, 1986), but not by truncated IBB or reverse NLS (SLN) controls (Fig+ 1B, lanes 5-12)+ The behavior of PHAX was similar to that of CBP80, which contains a classical bipartite NLS (Izaurralde et al+, 1995b)+ These results indicate that PHAX is imported via the classical NLS pathway, that is, via the importin a/b heterodimer+ To roughly map the location of the PHAX NLS, the protein was divided into three parts (N: amino-acid residues 1-133, M: 134-262, C: 263-385), and each part was fused to GST to make the proteins too large to diffuse through the NPCs+ When these GST fusion proteins were injected into the cytoplasm, all of them moved to the nucleus, whereas GSTM10 stayed in the cytoplasm (Fig+ 1C)+ Nuclear import of the three proteins was severely inhibited by injection of IBB (data not shown)+ These results suggest that there might be at least three classical NLSs distributed throughout the PHAX primary sequence+…”
Section: Phax Is Imported Into the Nucleus Via The Classical Nls Pathwaymentioning
confidence: 99%
“…PHAX has to recycle to the nucleus to mediate multiple rounds of U snRNA export+ We have previously shown that PHAX moves into the nucleus upon injection into the cytoplasm of Xenopus oocytes, whereas it is not apparently exported upon injection into the nucleus in the absence of U snRNAs (Ohno et al+, 2000; see also below)+ This means that although PHAX can shuttle between the nucleus and the cytoplasm, its steadystate localization in Xenopus oocytes is nuclear+ To investigate if this is also the case in mammalian cells, we performed indirect immunofluorescence staining of HeLa cells with affinity purified anti-PHAX antibody+ As shown in Figure 1A, strong PHAX signal was detected in the nucleoplasm (excluding nucleoli) with little if any cytoplasmic signal, indicating that nuclear localization of PHAX at steady state is not a Xenopus oocytespecific phenomenon+ Although the nucleoplasmic staining was not entirely uniform, and several brighter spots were often seen, further analysis of PHAX distribution has not been performed+ Next, attempts were made to characterize the nuclear localization signal (NLS) of PHAX in Xenopus oocyte injection experiments+ When 35 S-methionine labeled PHAX was injected into the cytoplasm together with two control proteins, PHAX, as well as the positive control CBP80, moved to the nucleus, whereas the negative control (GSTM10) stayed in the cytoplasm (Fig+ 1B, lanes 1-4)+ Nuclear migration of PHAX was severely inhibited by coinjection of either the importin b binding domain of importin a (IBB; Görlich et al+, 1996a;Weis et al+, 1996) or BSA-conjugated with NLS peptides derived from SV40 T antigen (BSA-NLS; Goldfarb et al+, 1986), but not by truncated IBB or reverse NLS (SLN) controls (Fig+ 1B, lanes 5-12)+ The behavior of PHAX was similar to that of CBP80, which contains a classical bipartite NLS (Izaurralde et al+, 1995b)+ These results indicate that PHAX is imported via the classical NLS pathway, that is, via the importin a/b heterodimer+ To roughly map the location of the PHAX NLS, the protein was divided into three parts (N: amino-acid residues 1-133, M: 134-262, C: 263-385), and each part was fused to GST to make the proteins too large to diffuse through the NPCs+ When these GST fusion proteins were injected into the cytoplasm, all of them moved to the nucleus, whereas GSTM10 stayed in the cytoplasm (Fig+ 1C)+ Nuclear import of the three proteins was severely inhibited by injection of IBB (data not shown)+ These results suggest that there might be at least three classical NLSs distributed throughout the PHAX primary sequence+…”
Section: Phax Is Imported Into the Nucleus Via The Classical Nls Pathwaymentioning
confidence: 99%
“…NRc~ was purified from Xenopus egg extracts as an essential protein for NLS-dependent binding of a fluorescent transport substrate to the NE and subsequent import into HeLa cell nuclei [11]. NRc~ is found in a complex with NRI3 [17,12,13,18,19]. Both subunits are required for binding and transport [17,20].…”
Section: Nls-reeeptor (Nr)mentioning
confidence: 99%
“…NR[3 was found to have weak [17] or no NLS-binding activity by itself [31,32] but it cooperates with NRc~ in NLS-recognition and binding of import substrate to the NE [16,17,32]. A large domain of so-called arm repeats [33] within NRc~ is responsible for NLS-binding [19,25]. NRa has eight repeats [11,34] whereas NR[3 has a number of less well defined repeats.…”
Section: Nls-reeeptor (Nr)mentioning
confidence: 99%
See 2 more Smart Citations